Internet connectivity disruption in Ireland (Ireland) - Voidly (2026)
CRITICAL severity disruption detected in Ireland. Confidence: 75%. Data sourced from IODA.
Network Disruption Incident ID: IE-2026-0011
Keywords: internet disruption; IE; disruption; critical